Annona muricata leaves have strongest cytotoxic activity against breast cancer cells - Susi Endrini; Suherman Suherman; Wahyu Widowati (Faculty of Medicine, Universitas Trisakti, 2014)
BACKGROUND Plant-derived herbal compounds have a long history of clinical use, better patient tolerance and acceptance. They are freely available natural compounds that can be safely used to prevent various ailments. Plants have been the basis of traditional medicine throughout the world for thousands of years and are providing mankind with new remedies. The objective of this study was to determine the cytotoxicity of soursop (Anona muricata Linn) leaves and pearl grass (Hedyotis corymbosa (L.) Lam.) on the hormone-dependent human breast carcinoma Michigan Cancer Foundation-7 (MCF-7) cell line. METHODS This study used two types of solvents (water and ethanol) in the extraction process and two incubation times (24 hours and 48 hours) in the MTT assays to analyze the cytotoxic effects of both plants. RESULTS Preliminary results showed that the ethanolic extract of soursop leaves (SE) displayed cytotoxic effects against MCF-7 on 24- and 48-hour incubation times with IC50 values of 88.788 μg/ml and 14.678 μg/ml, respectively. Ethanolic pearl grass extract (PE) showed similar results, with IC50 values of 65.011 μg/ ml on 24-hour incubation time and 52.329 μg/ml on 48-hour incubation time against MCF-7 cell line. However, the water extract of both plants displayed lower cytotoxic effect against MCF-7 cell line. CONCLUSION The ethanolic extract of both plants displayed cytotoxic effect against MCF-7. Soursop (Anona muricata Linn) leaves have the strongest cytotoxic activity against MCF-7 breast cancer cell line.